Alterations in Systemic Inflammatory Response Following a Half-Marathon Race with a Combined Curcumin and Pomegranate Supplement: A Feasibility Study. (23rd August 2021) - Tanner, Elizabeth A.; Gary, Melody A.; Davis, Asheal A.; Michalik, Stephan; McFarlin, Brian K.
Abstract: Endurance running training can lead to gradual accumulation of inflammation and soreness ultimately resulting in overuse injuries. Management of soreness and inflammation with pharmaceuticals (i.e. non-prescription pain relievers) during long-term training is not a suitable solution due to known side effects (e.g. gastrointestinal complications, etc.). Dietary polyphenols (i.e. curcumin, pomegranate, etc.) have been purported to reduce inflammation and muscle soreness, without these negative side effects making them ideal for use in an exercise model. The purpose of the present feasibility study was to explore the combined effect of optimized curcumin and pomegranate extract supplementation prior to (PRE) and after (4H and 24H) an organized half-marathon race on blood inflammatory proteins and inflammation-associated RNA. Daily supplementation (1000 mg/d) started 26 days before a half-marathon which doubled on days 27-31. Data were analyzed with R software and Welch t-test, significance set at p < 0.05. At both 4H and 24H, supplementation was associated with alterations in protein (IL-10, IL-13, IL-4, ITAC, MIP-1alpha, MIP-3alpha, BDNF, sIL-2Ralpha, and TNF-alpha; p < 0.05) and RNA (CCL22, GUSB, IL-6, LINC00305, NKILA, PTGES, THRIL, TRAF6, ARG2, CD1A, CD55, CFI, CSF2, CXC3CL1, CX3CR1, EDNRB, GATA3, LILRB5, THY1, CD3D, MRC1, GPR183, HAMP, MBL2, CASP3, B2M, KLRF2, PDCD1LG2, IL-10, PTGS2, TLR2, IL-6R, IL-8, IL-7R, MASP1, MYD88, TNFRSF1B, TNFRSF1A, and TIRAP; p < 0.05) biomarkers compared to control. Pathway classification of these biomarkers indicated supplementation may be associated with a more favorable muscle recovery profile. Our findings support the notion that combined curcumin and pomegranate supplementation may represent a useful addition to a comprehensive exercise training plan.